A Virtual Clinic Improves Pneumococcal Vaccination for Asplenic Veterans at High Risk for Pneumococcal Disease. (3rd November 2015) - Jump, Robin L.; Banks, Richard; Wilson, Brigid; Montpetite, Michelle M.; Carter, Rebecca; Phillips, Susan; Perez, Federico
Abstract: We developed a "virtual clinic" to improve pneumococcal vaccination among asplenic adults. Using an electronic medical record, we identified patients, assessed their vaccination status, entered orders, and notified patients and providers. Within 180 days, 38 of 76 patients (50%) received a pneumococcal vaccination. A virtual clinic may optimize vaccinations among high-risk patients.